2022
DOI: 10.1007/s15010-022-01758-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of COVID-19 infection post-vaccination: a survey among Indian doctors

Abstract: Purpose The rollout of COVID-19 vaccines began in India in January 2021, with healthcare professionals being the first to receive vaccination. The purpose of this research was to study the incidence and severity of COVID-19 infections among Indian doctors, following vaccination with ChAdOx1 nCoV-19 or BBV152. Methods We conducted an online voluntary survey among Indian doctors who received one or two doses of ChAdOx1 nCoV-19 or BBV152. Questions pertaining to the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In the study, male participants were more infected with COVID-19 than females and even males had acquired more COVID-19 infection following vaccination when compared to female participants. These findings were in concurrence with the findings of the study conducted by Parmeshwaran et al 8 In the present study, vaccinated participants with preexisting illnesses reported greater incidence of COVID-19 infection following vaccination and also the participants with recommended complete doses had a significantly lesser rate of COVID-19 infection post vaccination compared to those with partial doses of the respective vaccine. These results were similar to the study of Parmeshwaran et al 8 The present study also revealed reduced incidence (p<0.05) of COVID-19 infection post vaccination among participants who had history of past COVID-19 infection before the receipt of vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…In the study, male participants were more infected with COVID-19 than females and even males had acquired more COVID-19 infection following vaccination when compared to female participants. These findings were in concurrence with the findings of the study conducted by Parmeshwaran et al 8 In the present study, vaccinated participants with preexisting illnesses reported greater incidence of COVID-19 infection following vaccination and also the participants with recommended complete doses had a significantly lesser rate of COVID-19 infection post vaccination compared to those with partial doses of the respective vaccine. These results were similar to the study of Parmeshwaran et al 8 The present study also revealed reduced incidence (p<0.05) of COVID-19 infection post vaccination among participants who had history of past COVID-19 infection before the receipt of vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…In participants with prior viral exposure, two doses of BBV152 accorded sufficient protection, with an 87% efficiency against symptomatic reinfection, while a single dose was only 16% effective ( 43 ). A questionnaire-based study of health-care workers reported significantly reduced incidence and severity of COVID-19 infection in those receiving two doses of both Covaxin and Covishield compared to a single dose of either vaccine ( 44 ). Kumar et al.…”
Section: Discussionmentioning
confidence: 99%
“…While much research has been done on risk factors for SARS-CoV-2 infection in unvaccinated populations, risk factors for breakthrough infection in vaccinated individuals are less well understood and existing studies present conflicting findings. Whereas some studies have reported a higher risk of breakthrough infection among individuals with comorbidities, 9,10 other large-scale studies have found no associations with pre-existing conditions. 2 Similarly, several studies have suggested that older age is associated with increased risk of breakthrough infections, 11,12 whereas others have found no association 13,14 or an inverse association.…”
Section: Introductionmentioning
confidence: 97%
“…2 Similarly, several studies have suggested that older age is associated with increased risk of breakthrough infections, 11,12 whereas others have found no association 13,14 or an inverse association. 2 Most studies on risk of breakthrough infection have been limited to specific subgroups, 10,13,15 focused solely on severe outcomes, 16,17 or only considered infections before a booster dose. 2,9 Additionally, the few studies considering behaviours, such as levels of physical activity or journeys on public transport, have relied on baseline values, 2 and so have been unable to capture changes in behaviour that may have occurred over the various stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%